(untitled) (REMUNOM, 2025)
Several authors argue that the curriculum should be structured so as not to be based on isolated disciplines, reflecting the complexity of the contemporary world through a multifaceted perspective. Interdisciplinarity is one way to achieve this, and therefore, the interaction between the different areas of knowledge becomes fundamental today, as it contrasts with traditional teaching that divides knowledge into parts. In this context, the research in question aims to analyze interdisciplinary practices developed in schools and the results obtained, as well as to emphasize their relevance for teaching. In terms of methodology, the study is characterized as a bibliographic research with a qualitative approach. For data collection, material already prepared and published on the subject in vogue was used. To analyze the data, free interpretation analysis was followed. The results indicate that interdisciplinarity is an educational approach that seeks to integrate different disciplines to overcome the fragmentation of knowledge. Originating in the 1960s and 1970s, it aims to connect different knowledge without creating new disciplines, providing a more holistic view. Despite conceptual variations, there is a consensus on the importance of dialogue between areas of knowledge. Its implementation requires changes in pedagogical practices, involving everyone in the educational process. Interdisciplinarity enriches learning, adapting teaching to the needs of the contemporary world, and is of utmost importance in the area of ​​education. Among its other contributions, it is emphasized that interdisciplinarity in teaching has shown great importance, as it contributes to more meaningful and contextualized learning, integrating knowledge from different areas. This approach allows students to understand phenomena in a more holistic way, overcoming the fragmentation of traditional teaching. The use of interdisciplinary practices also benefits teaching practice and improves the performance of students with learning difficulties.